On state regulation issues ensuring energy savings in construction - Doroshenko, V. (Ways to Improve Construction Efficiency, 2019)
The article is aimed at studying the current state of state regulation from the point of view of ensuring energy saving in construction (regulatory case "On the energy efficiency of buildings"). The problem of state regulation of energy saving in construction is considered on the basis of a systematic approach in the context of three key components - institutes, regulation, tools. As a result of this study, state regulation of energy saving in the context of harmonization of European requirements for energy consumption reduction in buildings is described in more detail.